The effects of elemene emulsion injection on rat fecal microbiota and metabolites: Evidence from metagenomic exploration and liquid chromatography-mass spectrometry - Gu, Lei; Wu, Hao; Zhang, Yang; Wu, Yousheng; Jin, Yuan; Li, Tian; Ma, Litian; Zheng, Jin (Frontiers in Microbiology, 2022)
Objective: In this study, we investigated the effects of injection of elemene emulsion on the fecal microbiota and metabolites in Sprague Dawley (SD) rats. Methods: We randomly assigned 8 male SD rats to two groups, each with four rats: a control group (group C) and an elemene emulsion injection group (group L). Group L was intraperitoneally injected with elemene emulsion (40 mg/kg/d) for 14 consecutive days, and group C was intraperitoneally injected with the same volume of normal saline. Feces of each animal were then collected on day 14 post-dose for 16S rRNA gene amplification and sequencing, as well as fecal metabolomic analysis. Results: Injection of Elemene emulsion can alter the β-diversity of fecal microbiota, but not the α-diversity, and can induce structural changes in the fecal flora. In bacterial with significant changes in relative abundance at the genus level, elemene emulsion injection significantly inhibited most bacteria, but could up-regulated the relative abundance of unclassified Desulfovibrionales and Sulfurimonas. It could also upregulate 9 metabolites (hypoxanthine, tetradecane, L-Ornithine, xanthine, 6-aminonicotinic acid, 5,8,11,14-eicosatetraenoic acid, diisopropanolamine, ISD H-Phe(2-Cl)-OH and 2-aminoisobutyric acid). Additionally, we found a strong correlation between the fecal microbiota and potential biomarkers. Conclusion: Intraperitoneal injection of elemene emulsion modulates the composition of rat fecal microbiota and fecal metabolites.